Nigeria : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper discusses promotion of economic transformation in Nigeria. Nigeria's long-term potential is keyed on promoting economic transformation. This implies taking stock of initial conditions, assessing long-term financing capacity, and evaluating the policies and reforms to be implemented to meet the long term vision. The recent fall in prices has highlighted the challenging but compelling need to address remaining development challenges. This paper discusses some of these development imperatives including current regional disparities and ongoing policy initiatives, capacity to finance infrastructure needs, promoting domestic saving through developing financial inclusion, and the opportunity cost of quasi-fiscal activities.